Quantifying the Macroeconomic Impact of Covid-19-Related School Closures through the Human Capital Channel - Christine de la Maisonneuve; Balazs Egert; David Turner (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper uses a new measure of human capital, which distinguishes both quality and quantity components, to estimate the long-term effect of the Covid-19-related school closures on aggregate productivity through the human capital channel. Productivity losses build up over time and are estimated to range between 0.4% and 2.1% after 45 years, for 12 weeks and 2 years of school closure, respectively. These results appear to be broadly consistent with earlier findings in the literature. Two opposing effects might influence these estimates. Online teaching would lower economic costs while learning losses in tertiary education (not considered here) would inflate them. Policies aimed at improving the quality of education and adult training will be needed to offset or, at least, alleviate the impact of the pandemic on human capital.
Keywords: E24; I19; I20; I25; I26; I28; 330; Covid-19; human capital; PISA; PIAAC; productivity; education policies; OECD countries